The effect of ethanol on hexokinase from Saccharomyces cerevisiae Y102 - Foster, Edward J. F.(Edward James Freddy) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1984.